2016
DOI: 10.1016/j.jpain.2015.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Clinically Effective Treatment of Fibromyalgia Pain With High-Definition Transcranial Direct Current Stimulation: Phase II Open-Label Dose Optimization

Abstract: Despite promising preliminary results in treating fibromyalgia (FM) pain, no neuromodulation technique has been adopted in clinical practice because of limited efficacy, low response rate, or poor tolerability. This phase II open-label trial aims to define a methodology for a clinically effective treatment of pain in FM by establishing treatment protocols and screening procedures to maximize efficacy and response rate. High-definition transcranial direct current stimulation (HD-tDCS) provides targeted subthres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
95
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 113 publications
(104 citation statements)
references
References 44 publications
3
95
1
1
Order By: Relevance
“…It has been shown that a minimum of 10-20 sessions of tDCS need to be performed in order to induce relevant clinical improvements [39][40][41][42]. However, in clinical trials involving patients with severe disabilities, such as SCI as in the present study, we experienced a high rate of drop-out which limits the power of clinical results.…”
Section: Adherence To Extended Tdcs Protocolmentioning
confidence: 86%
“…It has been shown that a minimum of 10-20 sessions of tDCS need to be performed in order to induce relevant clinical improvements [39][40][41][42]. However, in clinical trials involving patients with severe disabilities, such as SCI as in the present study, we experienced a high rate of drop-out which limits the power of clinical results.…”
Section: Adherence To Extended Tdcs Protocolmentioning
confidence: 86%
“…In contrast, some studies found that M1-SO applied tDCS does not improve clinical pain outcomes [53]. Five sessions could be underdosing and may have limited treatment effects [54]. However, it is important to note that the efficacy of M1-SO tDCS depends on a number of factors, including the intensity and duration of stimulation, the polarity of the electrode, the target brain area, electrode preparation methods, and the target population [18].…”
Section: Discussionmentioning
confidence: 99%
“…Another possible explanation could be a type II error (β), since these measurements were secondary outcomes and our sample size was powered to detect qEEG differences. In addition, it should be noted that current literature on tDCS has shown that repetitive sessions are required in order to induce larger effects [36,37]. Therefore, a single stimulation session might not be enough to generate important clinical changes.…”
Section: Discussionmentioning
confidence: 99%